The Effects of 30 Minutes of Artificial Gravity on Cognitive and Sensorimotor Performance in a Spaceflight Analog Environment - Tays, Grant D.; McGregor, Heather R.; Lee, Jessica K.; Beltran, Nichole; Kofman, Igor S.; De Dios, Yiri Eleana; Mulder, Edwin; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Wood, Scott J.; Seidler, Rachael D. (Frontiers in Neural Circuits, 2022)
The altered vestibular signaling and somatosensory unloading of microgravity result in sensory reweighting and adaptation to conflicting sensory inputs. Aftereffects of these adaptive changes are evident postflight as impairments in behaviors such as balance and gait. Microgravity also induces fluid shifts towards the head and an upward shift of the brain within the skull; these changes are well-replicated in strict head-down tilt bed rest (HDBR), a spaceflight analog environment. Artificial gravity (AG) is a potential countermeasure to mitigate these effects of microgravity. A previous study demonstrated that intermittent (six, five-minute bouts per day) daily AG sessions were more efficacious at counteracting orthostatic intolerance in a five day HDBR study than continuous daily AG. Here we examined whether intermittent daily AG was also more effective than continuous dosing for mitigating brain and behavioral changes in response to 60 days of HDBR. Participants (n=24) were split evenly between three groups. The first received 30 minutes of continuous AG daily (cAG). The second received 30 minutes of intermittent AG daily (6 bouts of 5 minutes; iAG). The third received no AG (Ctrl). We collected a broad range of sensorimotor, cognitive, and brain structural and functional assessments before, during, and after the 60 days of HDBR. We observed no significant differences between the three groups in terms of HDBR-associated changes in cognition, balance, and functional mobility. Interestingly, the intermittent AG group reported less severe motion sickness symptoms than the continuous group during centrifugation; iAG motion sickness levels were not elevated above those of controls who did not undergo AG. They also had a shorter duration of post-AG illusory motion than cAG. Moreover, the two AG groups performed the paced auditory serial addition test weekly while undergoing AG; their performance was more accurate than that of controls, who performed the test while in HDBR. Although AG did not counteract HDBR-induced gait and balance declines, iAG did not cause motion sickness and was associated with better self-motion perception during AG ramp-down. Additionally, both AG groups had superior cognitive performance while undergoing AG relative to controls; this may reflect attention or motivation differences between the groups.